Técnica de energía muscular en la fisioterapia del manguito rotador. Hospital general IESS-Riobamba, 2018 – 2019 - Hernández Herrera, Miguel Fabricio (2019)
The rotator cuff is the set of muscles and their tendons that surround the shoulder, fulfill the function of stabilizing and giving very complex movements, understand their function and composition will help to know their predisposition to certain types of injuries. This anatomical region not only undertakes to be injured by sporting activities, but also by activities of daily or work life, where previous conditions, falls, tears and age are added to cause injuries or breakages. This investigative work has as main object of study to verify the rehabilitation of the rotator cuff by means of the technique of muscular energy in the physiotherapy of the cuff. General Hospital IESS-Riobamba, 2018 – 2019, this hospital entity was chosen due to the large number of patients with this pathology, 27 patients were included in the study, the same ones that were classified in two gender groups to identify in which of These have a higher incidence. The clinical history that included the anamnesis was carried out to obtain the information about his occupation, the physical examination and evaluation with the different tests, to identify the cause of the lesion and the exact treatment. Finally, a statistical analysis was carried out, compared the obtained data, in which it was recognized that the applied technique decreases the pain, with the analogue visual scale, the muscular strength and the different tests applied the necessary information was recorded. Therefore it demonstrated the effectiveness of the technique on other conventional ones.